A OPTIMIZATION OF THE SAFETY RIDING TO REDUCE THE OCCURRENCE OF ACCIDENTS TO ACHIEVE SECURITY, SAFETY, ORDER AND SMOOTH TRAFFIC IN THE GROBOGAN POLICE JURISDICTION - Ahasyweros Simbolon (Police Studies Review, 2022)
Security, safety, order, and smoothness in traffic is a situation and condition that is desired by all road users. However, with the development of people's lives and economy, it will have an impact on increasing the number of vehicles and movement on the streets. Meanwhile, the area and volume of the road did not increase, coupled with the factors of road conditions, vehicles and the environment that influence each other. Grobogan is the second largest district in Central Java and is a growing district known for its damaged roads and high accident rate. Public education with Safety Riding aims as an early prevention so that people attach importance to how to drive safely from each individual. The Kamsel Unit Grobogan Police continues to strive to optimize the Safety Riding for the community with methods and innovations that are continuously updated so that people understand more and understand that it is not about being able to drive, but about how to be safer driving. In this study using qualitative research methods by collecting data described in the form of statements or language. The research approach uses inductive analysis, namely by testing a theory in problem solving through data descriptions. Using Management Theory from George R. Terry as an analyst based on the Law on LLAJ to obtain the expected conditions and solutions to the problem. Program Safety Riding by the Kamsel Unit which has been carried out based on theoretical and regulatory analysis, it is still found that there are deficiencies in the management stage so that it is not optimal. So, to optimize the program to reduce accidents, it can be done by equipping the equipment with interesting methods which, if carried out by competent members in the field of traffic, can certainly optimize this program.